Science/STEM Librarianship in 2020: Opportunities and Insight. Issue 4 (1st October 2020) - Sterner, Elizabeth
ABSTRACT: The aim of this study is to offer an updated snapshot of current science/STEM opportunities in 2019/2020. The insight provided by the analysis of job announcements and a survey of current science/STEM librarians can assist new and current librarians looking for a position, recruiters hiring for a position, and professors reevaluating their MLIS/MLS curriculum. This study found that most positions are for full-time, permanent positions at an academic library located in the Midwest and on the East coast. Most of the positions are for research librarians with liaison duties in medicine/health science, mathematics, engineering, chemistry, and physics. A majority of the positions requires a Master's degree in library and information science from a program accredited by the American Library Association, and about half of the positions require or prefer a background in a related science/STEM field. While there is still no strong consensus on the necessity of a subject background and the responsibilities as a whole have not greatly changed, a demonstrated commitment to diversity, equity, and inclusion is now a common requirement. This study also highlights the top required skills and responsibilities and identifies insight and advice offered by current science/STEM librarians to future science/STEM librarians.